KERAGAMAN PLASMA NUTFAH PADI LOKAL ASAL KALIMANTAN UTARA - Tati Hariyati (Musamus University, 2019)
Bulungan is one of the regencies in North Kalimantan that has a high potential for land rice germplasm, with many species of rice cultivated by local people hereditary following their ancestors, on the other hand the naming follows the local community language tribe namely Dayak, Tidung and Bulungan, this study aims to obtain superior local rice varieties in assembling new varieties in the district of Bulungan, and to determine the characterization of local rice that can be used to support the development of food security. The qualitative research method is descriptive by purposive sampling which involves three stages, namely the first stage survey of rice planting areas, the second stage of exploration by conducting local rice cultivator inventorying in Bulungan. Results of local rice data in Bulungan District amounted to 69 local rice cultivars. The characteristics of local rice grain have diversity based on classification of shape, color, and size. Grain that is difficult to fall out and whether or not there is a tail in the grain. Keywords: Diversity, Land Rice, Bulungan, North Borneo